2001
DOI: 10.1007/bf03343808
|View full text |Cite
|
Sign up to set email alerts
|

Pituitary abscess presenting with cranial nerve paresis. Case report and review of literature

Abstract: Non-adenomatosus lesions of the pituitary represent a small part of the intrasellar processes and they have heterogeneous presentation. Making a precise diagnosis is of great importance, as it may lead to more efficient management. A 65-year-old man was admitted to the hospital because of headache and right cranial nerve III palsy. Basic laboratory work-up was normal whereas endocrinological assessment revealed hypopituitarism without diabetes insipidus. Plain radiography showed an enlarged sella and frontal a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…Vates et al reported 24 cases drawn from a series of more than 3500 patients who underwent pituitary surgery [2]. [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22], and a summary of these cases, which we selected for analysis, has been tabulated in Table 2, 3 and 4.…”
Section: Discussionmentioning
confidence: 99%
“…Vates et al reported 24 cases drawn from a series of more than 3500 patients who underwent pituitary surgery [2]. [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22], and a summary of these cases, which we selected for analysis, has been tabulated in Table 2, 3 and 4.…”
Section: Discussionmentioning
confidence: 99%
“…An acute sinus infection spreading to the pituitary region has been documented as a cause for pituitary abscess formation, and it is often a result of direct extension from the sphenoid sinus. 4 5 6 …”
Section: Introductionmentioning
confidence: 99%